PENGEMBANGAN INSTRUMEN PENILAIAN HIGHER ORDER THINKING SKILL (HOTS) PADA PEMBELAJARAN TEMA 8 (BUMIKU) DI KELAS VI SEKOLAH DASAR GUGUS III KECAMATAN GEROKGAK - astra arsiana, kadek evan; Yudiana, Kadek; Antara, Putu Aditya (Journal for Lesson and Learning Studies, 2022)
The assessment process carried out by teachers at this time is still not by the demands of 21st-century education. Some teachers use assessment instruments available on the internet without using the HOTS instrument. This study aimed to create a higher-order thinking skill (HOTS) assessment instrument for grade VI elementary school students. In this study, the development of the assessment instrument was guided by the Borg & Gall development model. In this study, the method used to collect data is the test method. The results of the content validity test tested by four expert lecturers of the HOTS assessment instrument were declared relevant, the item validity test conducted in 4 schools was declared valid, and the results of the reliability test of the HOTS assessment instrument were 0.82, which was in the very high category, the average test results The difference power of the questions is 0.43 which is in the excellent category, the average test results for the level of difficulty of the questions are 0.502 which are in the medium category. Based on this analysis, it can be said that the higher-order thinking skill (HOTS) assessment instrument in learning Theme 8 (Bumiku) in grade VI elementary school is feasible to use.